(untitled) (ENTHYMEMA, 2017)
This paper proposes a semiotic model for research in the field of Italian literature on the theme of work for the years 1995-2015. Focusing on Greimas’ theory of semiotic squares and on the actantial model, I focused on three basic relationships within the labour market: the contrast between stories in the context of the factory and the office, between local and global settings, and between the inclusion and exclusion of the worker-figure. I obtained a general structure of the story comprising a sequence of six events: admission, convocation, trauma (or loosening of work relationships), suspension, rescue (true or false), and inertia.